2022
DOI: 10.3390/ijerph19137910
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Model of Tourists’ Pro-Environmental Behavior Based on the Dual Path of Rational Planning and Embodied Emotion

Abstract: Tourists’ pro-environmental behavior is one of the key factors for the sustainable development of natural scenic spots. Although this behavior depends on the surroundings and context, the existing literature lacks the perspective of specific scenarios, especially that of embodied emotions. This research integrated the theory of planned behavior and embodied theory to construct an integrative model of pro-environmental behavior that combined tourists’ “rational planning” and “embodied emotion” and conducted an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 152 publications
2
15
0
Order By: Relevance
“…The following theoretical additions to the existing literature are illustrated by this investigation. Firstly, the study found that both the TPB and NAM models demonstrate significant explaining capacity on hikers' PEB in the protected areas, which further validates the findings of previous studies PEB (Han, 2015(Han, , 2021Alzubaidi et al, 2021;Aziz et al, 2021;Singh and Kaur, 2021;Cao et al, 2022;Kang, 2022;Long et al, 2022;Song et al, 2022;Zheng et al, 2022). Therefore, it is demonstrated that integrating TPB and NAM models is useful and effective for examining hikers' PEB in the protected areas and for understanding more fully the influence mechanism underlying such behavior.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 85%
See 2 more Smart Citations
“…The following theoretical additions to the existing literature are illustrated by this investigation. Firstly, the study found that both the TPB and NAM models demonstrate significant explaining capacity on hikers' PEB in the protected areas, which further validates the findings of previous studies PEB (Han, 2015(Han, , 2021Alzubaidi et al, 2021;Aziz et al, 2021;Singh and Kaur, 2021;Cao et al, 2022;Kang, 2022;Long et al, 2022;Song et al, 2022;Zheng et al, 2022). Therefore, it is demonstrated that integrating TPB and NAM models is useful and effective for examining hikers' PEB in the protected areas and for understanding more fully the influence mechanism underlying such behavior.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 85%
“…First, the results revealed that both the TPB model and NAM model displayed explanatory capacity on hikers' PEB in Wuyishan National Park in China. Scholars from a variety of disciplines have regularly evaluated the suitability of utilizing TPB or NAM models to explain PEB (Han, 2015(Han, , 2021Alzubaidi et al, 2021;Aziz et al, 2021;Singh and Kaur, 2021;Cao et al, 2022;Kang, 2022;Long et al, 2022;Song et al, 2022;Zheng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, many studies show that psychological factors are greater contributors to the formation mechanisms of PEB than external factors (Gao et al, 2023;Li et al, 2019). In response, the role of emotion in PEB has been increasingly emphasized over recent years, with variables such as nostalgia (Le, 2020), connectedness to nature (Cao et al, 2022) and landscape perception and emotions (Salim et al, 2023) being successively included in the framework of PEB research. Moreover, Li et al (2019) proposed the need to pay attention to the deep analysis of the formation mechanism of PEB and introduce more specific psychological factors in the research model based on the limitations of the current study.…”
Section: Self-congruity Theorymentioning
confidence: 99%
“…Tourists prefer to visit nature-based and rural destinations (Hardt & Glu ¨ckstad, 2024) and avoid urban tourist destinations (Huang et al, 2021). Promoting PEB among tourists minimizes the negative impacts of tourist growth on the natural environment, balancing economic development with natural environmental protection (Cao et al, 2022). As for tourism cities, sustainable destination management, including NBT destinations and destination branding, are also important tourism recovery strategies (Yang, Li, & Hern andez-Lara, 2022;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%